Sclerotherapy for Aneurysmal Bone Cysts: Scale for Response. Issue 7 (August 2021) - Ramkumar, Dipak B.; Ercolano, Lisa B.; Allar, Benjamin G.; Miller, Patricia E.; Padua, Horacio; Anderson, Megan E.
Abstract : Background: The objective of this study was to develop a response scale for aneurysmal bone cysts (ABCs) treated with sclerotherapy and determine its inter-rater reproducibility. Methods: Patients treated with sclerotherapy for an ABC between 1993 and 2014 were identified. An attending orthopaedic surgeon and an attending interventional radiologist independently reviewed the radiographic series for each patient and determined response to treatment using a novel grading system. Pain scores were collected from each visit. Inter-rater reliability was assessed using the intraclass correlation coefficient (ICC). General estimating equations analysis was used to evaluate the relationship between radiographic and pain scores and outcome, to develop an algorithm for the study patient population. A receiver operating characteristic curve was constructed to evaluate the diagnostic performance of the radiographic and pain scores in identifying the necessity of further treatment. To quantify the diagnostic utility, the area under the receiver operating characteristic curve was estimated along with a 95% confidence interval (CI). Results: The inter-rater reliability was excellent for magnetic resonance imaging (ICC=0.83; 95% CI=0.74-0.89) and good for computed tomography/x-ray (ICC=0.69; 95% CI=0.51-0.81). The radiographic and pain scores proved to be independent predictors of treatment ( P <0.001 and 0.004, respectively). An algorithm to determine the predictive probability for treatment versus observation in the study population was developed and tested based on these assessments. The area under the receiver operating characteristic curve of 0.85 (95% CI=0.79-0.92) indicated the good diagnostic performance of the algorithm. Conclusions: This novel grading system for radiographic response to sclerotherapy treatment demonstrates excellent to good inter-rater reliability giving providers a platform for discussion among themselves and with patients/parents. When incorporated with an assessment of pain, a predictive algorithm shows how this information could be used to determine the next steps after sclerotherapy treatment. Level of Evidence: Level IV—case series.